Kompetensi Manajerial Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pada SD Negeri 50 Kota Ternate - Fadillah Adnan; Said Hasan; Marwan Marwan (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
This study aims to 1). find out the ability of school principals to develop programs to improve teacher performance; 2) knowing the ability of the Principal in Carrying Out Activities to Improve Teacher Performance; and 3) knowing the ability of the Principal in Conducting Evaluations to Improve Teacher Performance. This study uses a descriptive method, namely a qualitative approach by uncovering certain social situations that describe reality correctly, formed by words based on relevant data collection and analysis techniques. The results of the study show that the principal has the ability to develop programs, carry out activities and carry out evaluations to improve teacher performance at SD Negeri 50 Kota Ternate.